Development of HOTs-Based Teaching Materials, Multiple Intelligence, and Baimbai Wood Characters for River-Bank Elementary Schools - Noorhapizah Noorhapizah; Diani Ayu Pratiwi; Yogi Prihandoko; Helwa Ayuni; Tri Ayu Saptaning Putri (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This study aims to develop teaching materials based on HOTS, multiple intelligence, and the character of Baimbai pedaling for riverside elementary schools. This study used the research and product development method of teaching materials with the Borg & Gall design, which consisted of 10 steps. The sample comprises 72 elementary school students, six principals, and 10 class teachers. The sampling technique used purposive random sampling. The research instrument is a validity test questionnaire and tests. Data analysis used qualitative data analysis and independent sample t-test. Based on the results of assessments from SD teaching materials experts, media experts, SD design experts, and character education experts, a score of > 92 was obtained, indicating that the teaching materials were feasible to use. Based on the results of the effectiveness test conducted on 46 students and analyzed using an independent sample t-test, the t-count value was higher than the t-table (2.231> 1.576), and the significance value was less than 0.05 (0.002 <0.005). The increase occurred in the medium category with a value of N-Gain = 0.39